Creditor's Responsibility for Forced Withdrawal of Fiduciary Objects After Constitutional Court Decision No. 18/PUU-XVII/2019 - Abyan, Nabil Luthfi; Rizkianti, Wardani (Magister Hukum Universitas Semarang, 2024)
This research aims to examine the changing dynamics of fiduciary security execution after Indonesian Constitutional Court Decisions No. 18/PUU-XVII/2019. The focus of this research lies on the creditor's responsibility in the context of forced withdrawal of the fiduciary object after the debtor's failure. This research uses a normative juridical research method with a legal source approach and case analysis. Through in-depth analysis of legal sources such as the constitution, laws, and relevant court decisions, this research identifies significant changes in the practice of fiduciary security execution. The case approach is used to understand the implementation of legal decisions in concrete situations. The results show that, in the case of a default agreement, parate execution can be an acceptable alternative, providing flexibility in settlement. However, when there is no agreement, court intervention is required to ensure fairness. This research provides a deeper understanding of the changes in the practice of fiduciary security execution, as well as a new outlook on creditor responsibilities and the need for adjustments in legal practice. Therefore, the novelty of this research lies in the in-depth understanding of creditor responsibilities in situations of forced withdrawal of fiduciary objects, especially after recent legal changes.